2014
DOI: 10.1603/ec11205
|View full text |Cite
|
Sign up to set email alerts
|

Life Parameters of <I>Tetranychus urticae</I> (Acari: Tetranychidae) on Six Common Bean Cultivars

Abstract: It is well recognized that the quality of host plants affects the development and survival of twospotted spider mite Tetranychus urticae Koch. The life table parameters of T. urticae, on six cultivars of common bean (Phaseolus vulgaris L.) (chiti Khomein, chiti Ks21189, red Akhtar, red Ks31169, white Pak, and white G11867) were studied at constant laboratory conditions (27 +/- 2 degrees C, 70 +/- 5% RH and 16:8 L:D). Total development times of immature males and females were significantly influenced by bean cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Because fewer females for each generation are produced by T. urticae females feed on the seven eggplant cultivars, the R o values were found to be much less than the favourable host plants i.e. beans (185.4), soybeans (59-66) and tomatoes (49-131) (Kasap 2002;Dehghan et al 2009;Atalay & Kumral 2013;Najafabadi et al 2014). In addition, both the r m and Ro values of T. urticae were found to be significantly higher in Aydin Siyahi and Kemer, Topan 374 and Yalova Topan cultivars compared with the values of the other cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Because fewer females for each generation are produced by T. urticae females feed on the seven eggplant cultivars, the R o values were found to be much less than the favourable host plants i.e. beans (185.4), soybeans (59-66) and tomatoes (49-131) (Kasap 2002;Dehghan et al 2009;Atalay & Kumral 2013;Najafabadi et al 2014). In addition, both the r m and Ro values of T. urticae were found to be significantly higher in Aydin Siyahi and Kemer, Topan 374 and Yalova Topan cultivars compared with the values of the other cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…The BD 08, BD 57, BD 17 and the Espanhola were moderately susceptible and the others showed low susceptibility to T. ludeni. The development of the mites may vary between the genotypes of the same species (Modarres Najafabadi et al, 2014) as reported for Amphitetranychus viennensis Zacher and Tetranychus urticae Koch (Acari: Tetranychidae) on apples (Kasap, 2003) and T. urticae on strawberry (Wold and Hutchison, 2003), cucumber (Park and Lee, 2007) and tomato (Keskin and Kumral, 2015). The total height, number of leafs, flowers and fruits and fruit weight were found to be lower on the eggplant (Solanum melongena L. Solanaceae) cultivar Panruti than on the other varieties of this plant (Reddy and Baskaran, 2006).…”
Section: Resultsmentioning
confidence: 79%
“…According to the findings of Sedaratian et al (2008), different cultivars of soybean (Glycine max (L.) Merr., Fabaceae) can influence the bionomics of T. urticae; the authors noted a significant difference in T. urticae population density between seven soybean cultivars studied. Furthermore, Najafabadi et al (2014), found that the development and survive of T. urticae were influenced by quality of the host plant. This finding was observed through an evaluation conducted on six different cultivars of bean (Phaseolus vulgaris L., Fabaceae).…”
Section: Discussionmentioning
confidence: 99%